LANGKAH-LANGKAH PEMERINTAH DESA AIR EMAS KECAMATAN UKUI KABUPATEN PELALAWAN DALAM MEWAKILI PROVINSI RIAU PADA BULAN BAKTI GOTONG ROYONG MASYARAKAT (BBGRM) TINGKAT NASIONAL TAHUN 2017 - Prabowo, Nuryawan Eko; Amin, Raja Muhammad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
The steps of the success of the Air Emas Village Government to represent Riau Province in the 2017 national level Bakti Gotong Royong Masyarakat (BBGRM) Community Contest need to be appreciated and emulated by other villages where the success of Air Emas Village in 2017 at the National Level BBGRM competition is not free -steps that the village government applied. Therefore, it is necessary to know the steps in order to be able to make referrals by other villages. This study aims to analyze the steps taken by the government of the Golden Water Village in Ukui District, Pelalawan Regency so that they can represent Riau Province in the 2017 National Community Service Month Competition. This research uses a qualitative method with a descriptive approach. Data collection techniques used were interview techniques and documentation. The results of the study can be concluded that the steps of the Air Emas Village Government in representing Riau Province in the 2017 National Level Community Service (BBGRM) Month are collaborating with the government and PMD to form the BBGRM Village Implementation Team, conducting deliberations to determine and determine the fields that will be planned in BBGRM activities are planning various things related to BBGRM, both funding, regulations related to BBGRM, parties involved in the implementation of BBGRM, and parties that move the community to participate in mutual cooperation in BBGRM activities. As well as good coordination between village institutions and community leaders. Keywords: Steps of Village Government, Bulan Bakti Gotong Royong Masyarakat (BBGRM)